Low-level parental somatic mosaic SNVs in exomes from a large cohort of trios with diverse suspected Mendelian conditions. - Gambin, Tomasz; Liu, Qian; Karolak, Justyna A; Grochowski, Christopher M; Xie, Nina G; Wu, Lucia R; Yan, Yan Helen; Cao, Ye; Coban Akdemir, Zeynep H; Wilson, Theresa A; Jhangiani, Shalini N; Chen, Ed; et al. (Genet Med, 2020)
PURPOSE: The goal of this study was to assess the scale of low-level parental mosaicism in exome sequencing (ES) databases. METHODS: We analyzed approximately 2000 family trio ES data sets from the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) and Baylor Genetics (BG). Among apparent de novo single-nucleotide variants identified in the affected probands, we selected rare unique variants with variant allele fraction (VAF) between 30% and 70% in the probands and lower than 10% in one of the parents. RESULTS: Of 102 candidate mosaic variants validated using amplicon-based next-generation sequencing, droplet digital polymerase chain reaction, or blocker displacement amplification, 27 (26.4%) were confirmed to be low- (VAF between 1% and 10%) or very low (VAF <1%) level mosaic. Detection precision in parental samples with two or more alternate reads was 63.6% (BHCMG) and 43.6% (BG). In nine investigated individuals, we observed variability of mosaic ratios among blood, saliva, fibroblast, buccal, hair, and urine samples. CONCLUSION: Our computational pipeline enables robust discrimination between true and false positive candidate mosaic variants and efficient detection of low-level mosaicism in ES samples. We confirm that the presence of two or more alternate reads in the parental sample is a reliable predictor of low-level parental somatic mosaicism.
Keywords: Exome; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Whole Exome Sequencing

Quantitative Assessment of Parental Somatic Mosaicism for Copy-Number Variant (CNV) Deletions. - Liu, Qian; Grochowski, Christopher M; Bi, Weimin; Lupski, James R; Stankiewicz, Paweł (Curr Protoc Hum Genet, 2020)
As genome sequencing methodologies have become more sensitive in detecting low-frequency rare-variant events, the link between post-zygotic mutagenesis and somatic mosaicism in the etiology of several human genetic conditions other than cancers has become more clear. Given that current clinical-genomics diagnostic methods have limited detection sensitivity for mosaic events, a copy-number variant (CNV) deletion inherited from a parent with low-level (<10%) mosaicism can be erroneously interpreted in the proband to represent a de novo germline event. Here, we describe three sensitive, precise, and cost-efficient methods that can quantitatively assess the potential degree of parental somatic mosaicism levels for CNV deletions: droplet digital PCR (ddPCR), PCR amplicon-based next-generation sequencing (NGS), and quantitative PCR. ddPCR using the EvaGreen fluorescent dye protocol can specifically quantify the deleted or non-deleted alleles by analyzing the number of droplets positive for a fluorescent signal for each event. PCR amplicon-based NGS assesses the allele frequencies of a heterozygous single-nucleotide polymorphism within a deletion region. The difference in number of reads between the two genotypes indicates the level of somatic mosaicism for the CNV deletion. Quantitative PCR can be applied where the relative quantity of the deletion junction-specific product represents the level of mosaicism. Clinical implementation of these quantitative variant-detection methods enables potentially more accurate assessment of disease recurrence risk in family-based genetic counseling, allowing couples to engage in more informed family planning. © 2020 by John Wiley & Sons, Inc. Basic Protocol: Droplet digital PCR (ddPCR) Alternate Protocol 1: PCR amplicon-based next-generation sequencing Alternate Protocol 2: Quantitative real-time PCR (qPCR).
Keywords: DNA Copy Number Variations; Genetic Diseases, Inborn; High-Throughput Nucleotide Sequencing; Humans; Mosaicism; Parents; Polymorphism, Single Nucleotide; Real-Time Polymerase Chain Reaction

Pathogenetics of alveolar capillary dysplasia with misalignment of pulmonary veins. - Szafranski, Przemyslaw; Gambin, Tomasz; Dharmadhikari, Avinash V; Akdemir, Kadir Caner; Jhangiani, Shalini N; Schuette, Jennifer; Godiwala, Nihal; Yatsenko, Svetlana A; Sebastian, Jessica; Madan-Khetarpal, Suneeta; Surti, Urvashi; Abellar, Rosanna G; et al. (Hum Genet, 2016)
Alveolar capillary dysplasia with misalignment of pulmonary veins (ACDMPV) is a lethal lung developmental disorder caused by heterozygous point mutations or genomic deletion copy-number variants (CNVs) of FOXF1 or its upstream enhancer involving fetal lung-expressed long noncoding RNA genes LINC01081 and LINC01082. Using custom-designed array comparative genomic hybridization, Sanger sequencing, whole exome sequencing (WES), and bioinformatic analyses, we studied 22 new unrelated families (20 postnatal and two prenatal) with clinically diagnosed ACDMPV. We describe novel deletion CNVs at the FOXF1 locus in 13 unrelated ACDMPV patients. Together with the previously reported cases, all 31 genomic deletions in 16q24.1, pathogenic for ACDMPV, for which parental origin was determined, arose de novo with 30 of them occurring on the maternally inherited chromosome 16, strongly implicating genomic imprinting of the FOXF1 locus in human lungs. Surprisingly, we have also identified four ACDMPV families with the pathogenic variants in the FOXF1 locus that arose on paternal chromosome 16. Interestingly, a combination of the severe cardiac defects, including hypoplastic left heart, and single umbilical artery were observed only in children with deletion CNVs involving FOXF1 and its upstream enhancer. Our data demonstrate that genomic imprinting at 16q24.1 plays an important role in variable ACDMPV manifestation likely through long-range regulation of FOXF1 expression, and may be also responsible for key phenotypic features of maternal uniparental disomy 16. Moreover, in one family, WES revealed a de novo missense variant in ESRP1, potentially implicating FGF signaling in the etiology of ACDMPV.
Keywords: Chromosomes, Human, Pair 16; Comparative Genomic Hybridization; Female; Forkhead Transcription Factors; Genes, Lethal; Genome, Human; Genomic Imprinting; High-Throughput Nucleotide Sequencing; Humans; Infant, Newborn; Male; Pedigree; Persistent Fetal Circulation Syndrome; Pulmonary Alveoli; Pulmonary Veins; Sequence Deletion